2018
DOI: 10.1021/acs.jafc.7b06135
|View full text |Cite
|
Sign up to set email alerts
|

Protective Effects of Blueberry Anthocyanins against H2O2-Induced Oxidative Injuries in Human Retinal Pigment Epithelial Cells

Abstract: Blueberry anthocyanins are considered protective of eye health because of their recognized antioxidant properties. In this study, blueberry anthocyanin extract (BAE), malvidin (Mv), malvidin-3-glucoside (Mv-3-glc), and malvidin-3-galactoside (Mv-3-gal) all reduced HO-induced oxidative stress by decreasing the levels of reactive oxygen species and malondialdehyde and increasing the levels of superoxide dismutase, catalase, and glutathione peroxidase in human retinal pigment epithelial cells. BAE and the anthocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 81 publications
(54 citation statements)
references
References 53 publications
4
50
0
Order By: Relevance
“…In this study, BAE protected RPE cells from visible lightinduced damage and reduced the intracellular ROS levels. A previous study shown that blueberry ACNs protected against H 2 O 2 -induced oxidative injuries in RPE cells (Huang et al, 2018). In addition, quercetin protected retinal cells from H 2 O 2 -and light-induced oxidative stress by inducing the expression of HO-1 (Saviranta et al, 2011;.…”
Section: Discussionmentioning
confidence: 88%
“…In this study, BAE protected RPE cells from visible lightinduced damage and reduced the intracellular ROS levels. A previous study shown that blueberry ACNs protected against H 2 O 2 -induced oxidative injuries in RPE cells (Huang et al, 2018). In addition, quercetin protected retinal cells from H 2 O 2 -and light-induced oxidative stress by inducing the expression of HO-1 (Saviranta et al, 2011;.…”
Section: Discussionmentioning
confidence: 88%
“…Blueberry anthocyanin extract (BAE) was obtained from rabbiteye blueberry fruits harvested by Fujiabian Orchard Picking (Lishui, Nanjing, China) [18]. Malvidin (Mv), malvidin-3-glucose (Mv-3-glc), malvidin-3-galactose (Mv-3-gal), and 3-4,5 dimethylthiazol-2,5 diphenyl tetrazolium bromide (MTT) were purchased from Sigma Aldrich (Shanghai, China).…”
Section: Materials and Chemicalsmentioning
confidence: 99%
“…In our previous study, malvidin was also confirmed as the largest anthocyanidin found in Brightwell rabbiteye blueberry (Vaccinium ashei) of Nanjing, mostly as malvidin-3-glucoside (Mv-3-glc) and malvidin-3-galactoside (Mv-3-gal) [17]. We tried to investigate the different bioactivities of blueberry anthocyanin extract as well as its major constituents Mv-3-glc and Mv-3-gal and found they could improve endothelial function by protecting against oxidative stress [18,19]. However, only a few reports are about the vasodilation activities of anthocyanin extract from blueberry fruits [20].…”
Section: Introductionmentioning
confidence: 99%
“…Black rice anthocyanins also induce cell proliferation and inhibit the apoptosis pathway [23]. Anthocyanin also promotes antiapoptotic effect on the human retinal pigment epithelial cells [24]. However, the mechanism is still unclear.…”
Section: Introductionmentioning
confidence: 99%